Toxicology Versus Allergy in Dental Materials - Fahad Mohammed Albakri; Dr.Hosain Almansour; Yousef Saleh Ali Al Mawtah; Ali Mohammed Al Salamah; Mosa Mohammad Alrifai (International Journal of Medical Toxicology and Legal Medicine, 2024)
Dental materials range from polymers to metals that are used to treat tooth decay, replace missing teeth, or even in orthodontic cases. Although all of these materials with a long history of use are tested for their biocompatibility in the oral cavity and their effective role in improving oral health. However, these materials may show side effects that may lead to severe infections or more serious diseases. This review provides an overview of dental materials Allergy and toxicity of different materials in dentistry